UPPER THORACIC SPINE (D2-D3) FRACTURE-DISLOCATION WITHOUT SPINAL CORD INJURY: A CASE REPORT - Kailash, Karthik; js, Rajkumar; Kalavakonda, Chandrasekar (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Fracture dislocations of the thoracic spine in extremly rare and when it occurs,it is considered the most unstable of spinal injuries and is almost always associated with injury to the spinal cord due to narrow spinal canal dimensions.Very few neurologically intact cases of thoracic spine fracture dislocation have been reported in the literature ,which are mostly around the dorsolumbar junction and none in the upper thoracic spine.Here we report a case of 44 years old man who was in a road traffic accident and diagnosed with fracture dislocation of D2 over D3 vertebra with no neurological deficit.Patient was treated with Posterior spinal stabilization,reduction and D2 laminectomy.Patient remanined neurologically intact post operatively.Here we discuss the significance of this injury and the neural sparing mechanism of posterior neural arch disruption(bilateral pedicle fracture and lamina fracture),which preserves the spinal canal and the spinal cord from being damaged.We also discuss about the usefulness of CT scan and MR imaging in these injuries and the surgical approaches used in treating them. Keywords-fracture dislocation,thoracic spine,surgical approaches